"Information technology act,rules and regulations" - "Kamath,Nandan" (New Delhi, 2001)
The dawn of the new millennium brings with it many challenges to the law as we know it. The advent of computers and the internet as legitimate channels for communication and information dissemination has resulted in a sea change.
Keywords: Information technology